A qualitative study of hand hygiene compliance among health care workers in intensive care units - Ay, Pinar; Teker, Ayse Gulsen; Hidiroglu, Seyhan; Tepe, Pinar; Surmen, Aysen; Sili, Uluhan; Korten, Volkan; Karavus, Melda (The Journal of Infection in Developing Countries, 2019)
Introduction: Studies indicate that adherence to hand hygiene guidelines is at suboptimal levels. We aimed to explore the reasons for poor hand hygiene compliance. Methodology: A qualitative study based on the Theory of Planned Behavior as a framework in explaining compliance, consisting four focus group discussions and six in-depth interviews. Results: Participants mostly practiced hand hygiene depending on the sense of "dirtiness" and "cleanliness". Some of the participants indicated that on-job training delivered by the infection control team changed their perception of "emotionally" based hand hygiene to "indication" based. Direct observations and individual feedback on one-to-one basis were the core of this training. There was low social cohesiveness and a deep polarization between the professional groups that led one group accusing the other for not being compliant. Conclusions: The infection control team should continue delivering one-to-one trainings based on observation and immediate feedback. But there is need to base this training model on a structured behavioral modification program and test its efficacy through a quasi-experimental design. Increasing social cohesiveness and transforming the blaming culture to a collaborative safety culture is also crucial to improve compliance. High workload, problems related to work-flow and turnover should be addressed.